POLITIK KETAHANAN NASIONAL - Muhammad Angga Ramdhan (Universitas Jenderal Ahmad Yani, 2019)
The rise of nationalism values among democratic election in Western Europe had brought back the trend of classical realism in current international relations. Brexit phenomena, in which Great Britain choose to withdraw from European Union membership, is not separated from the trend. The phenomena become interesting case studies when compared to Indonesian election in 2019 where national resilience becomes the political focus. Using classical realism, this article aimed to understand why populism movement based on national resilience values was accepted in Brexit referendum but insignificant in Indonesian election. From the inquiries, this article concludes that populism movement emphasizing threats and nationalistic approach works in Great Britain due to instability caused by migrant, while Indonesia was much stable due to stronger national resilience against threats.